Students’ Anxiety in Learning Englih (A Case Study at Eleventh Grade of SMK Al Istiqomah NW Mamben Baru) - Rifqi, Moh.; Nawawi; Junaidi, Ahmad; Ahmadi, Nur (Journal of English Education Forum (JEEF), 2024)
This study aims to investigate types of anxiety experienced by the students in learning English and factors that contribute to students’ anxiety in learning English in the Eleventh grade of SMK Al Istiqomah NW Mamben Baru. This is a qualitative descriptive research with a case study. The study was employed through observations, interviews, and documentation in data collecting. The data was analyzed through descriptive analysis. The result of the research showed that there were two types of anxiety were experienced by the students of Eleventh grade of SMK Al Istiqomah NW Mamben Baru in learning English, that were state anxiety and state anxiety. In term of causes there were three causes that contribute to students’ anxiety in learning English; firstly, was communication apprehension. Secondly was fear of negative evaluation. Thirdly is lack of vocabulary and grammar.